In step 1, y was made the subject of the second equation to get:
y=5x-4
To proceed, the next step is to substitute the expression into the other equation, not the equation we solved for y.
8x+2y=-12
8x+2(5x-4)=-12
8x+10x-8=-12
18x=-12+8
18x=-4
x=-
![(4)/(18)](https://img.qammunity.org/2023/formulas/mathematics/high-school/wk4unudwgz0rimsr0ot1tg3cr5n10bx392.png)
x=
![\frac-{2}{9}](https://img.qammunity.org/2023/formulas/mathematics/high-school/omadp19v28ifum5fqhgis4gdbq2pngkune.png)
answer= the value of x is -2/9